Statistical analysis of compressive strength of concrete specimens - Aguiar, J. L. Barroso de (2003)
This paper presents the statistical analysis of compressive strength of concrete specimens delivered in a laboratory of Northern of Portugal. Three types of concretes were analyzed defined as C20, C25 and C30. In the study we used the results of three years, 1995 to 1997. The one-sample Kolmogorov-Smirnov Test was used to verify the normal distribution of the strength results. The results presented in this paper are important for predicting the performance of structural elements and for calculating resistance factors for limit state design codes. As concrete is made in majority on site, conformity is more difficult than for other construction materials produced on factories. For the first analysis the concrete applied on the different sites were separated in groups. A total of 82 groups of concrete produced in 20 sites, were analyzed. We verified that in about 32% of the groups the characteristic compressive strength established for the design was not achieved. For the second analysis the total results were considered, without separation by site or by group. When the exigency was classes C20 or C25, the characteristic compressive strength was below the exigency. On the contrary, for the concrete mentioned as C30, the characteristic compressive strength was above the exigency.